Structure-guided design of a potent Clostridioides difficile toxin A inhibitor - Hussack, Greg; Rossotti, Martin A.; van Faassen, Henk; Murase, Tomohiko; Eugenio, Luiz; Schrag, Joseph D.; Ng, Kenneth K.-S.; Tanha, Jamshid (Frontiers in Microbiology, 2023)
Crystal structures of camelid heavy-chain antibody variable domains (VHHs) bound to fragments of the combined repetitive oligopeptides domain of Clostridiodes difficile toxin A (TcdA) reveal that the C-terminus of VHH A20 was located 30 Å away from the N-terminus of VHH A26. Based on this observation, we generated a biparatopic fusion protein with A20 at the N-terminus, followed by a (GS)6 linker and A26 at the C-terminus. This A20-A26 fusion protein shows an improvement in binding affinity and a dramatic increase in TcdA neutralization potency (330-fold [IC50]; 2700-fold [IC99]) when compared to the unfused A20 and A26 VHHs. A20-A26 also shows much higher binding affinity and neutralization potency when compared to a series of control antibody constructs that include fusions of two A20 VHHs, fusions of two A26 VHHs, a biparatopic fusion with A26 at the N-terminus and A20 at the C-terminus (A26-A20), and actoxumab. In particular, A20-A26 displays a 310-fold (IC50) to 29,000-fold (IC99) higher neutralization potency than A26-A20. Size-exclusion chromatography-multiangle light scattering (SEC-MALS) analyses further reveal that A20-A26 binds to TcdA with 1:1 stoichiometry and simultaneous engagement of both A20 and A26 epitopes as expected based on the biparatopic design inspired by the crystal structures of TcdA bound to A20 and A26. In contrast, the control constructs show varied and heterogeneous binding modes. These results highlight the importance of molecular geometric constraints in generating highly potent antibody-based reagents capable of exploiting the simultaneous binding of more than one paratope to an antigen.